Neonatal Surgery: Demand and Survival Both are Increasing: Eight Years Experience in Dhaka Medical College Hospital, Bangladesh (Journal of Paediatric Surgeons of Bangladesh, 2014)
Purpose: In order to achieve the Millennium Development Goal (MDG) 4 target of a two-thirds reduction in under-five mortality from 1990 to 2015, major reductions are going to be required in neonatal mortality. Congenital anomalies have become the fourth cause of neonatal deaths and most of these are curable. Dhaka Medical College Hospital is the largest public hospital of the country and serving the poor and lower middle class people where surgery and medical facilities are mostly free of cost. This study was done to see the types of neonatal surgical patients admitted in this hospital and their management out come with limited facilities and find out the ways to improve the scenario to contribute in achieving the MDG.Materials & Methods: This was a retrospective study done over a period of 8 years from July 2001 to June 2009 and carried out in the Department of Pediatric Surgery, Dhaka Medical College Hospital, Dhaka. A total of 650 neonates were admitted during this period and it was the 17.99% of total number of 3612 pediatric surgical admission upto12 years of age. Data was collected from hospital records and analyzed retrospectively.Results: Out of these 650 neonates 533(80%) were admitted for Neonatal Intestinal Obstruction (NIO) and omphalocele were 59 (9.07%), ectopia vesicae are 14 (2.15% ), posterior urethral valves (PUV) were 19 (2.92%), gastroschisis were 7 (1.07%) , congenital diaphragmatic hernia (CDH) were 16 (2.46%),Tracheo-oesophageal fistula 1 (0.15%), and Conjoint twin 1 (0.15%). The most common cause of NIO was anorectal malformation (ARM) and 194 (66.43%) patients have high variety and 98(33.56%) patients have low variety ARM. Next was Hirschsprung disease and 137 (21.07%) neonates presented with this. Thirty-Five (5.38%) patients presented with septicemia and 40 (6.15%) presented with intestinal atresia, 20 (3.07%) neonates had meconium ileus and 9 (1.38%) patients presented with volvulus neonatorum. Five hundred and Fifty-nine patients (86.00%) were managed surgically. Out of 650 patients, 69 died, so mortality was 10.61% and before surgery 2.76% and after surgery was 7.84%.Conclusion: Pediatric surgeons by their skill and teamwork greatly improved the neonatal surgical service and contributing significantly in reducing infant mortality rate and to achieve MDG 4. But to improve further, neonatal intensive care unit (NICU) and other support systems are essential as well as support from UNICEF and World Health Organization (WHO) to include pediatric surgery and surgeons in their activities especially in developing countries. Due to socio-political and economic reasons of the developing countries the roll of pediatric surgeons are multidimensional.DOI: http://dx.doi.org/10.3329/jpsb.v1i1.19463